Efficient isolation of targeted Caenorhabditis elegans deletion strains using highly thermostable restriction endonucleases and PCR - Wei, Aguan (Oxford University Press, 2002)
Reverse genetic approaches to understanding gene function would be greatly facilitated by increasing the efficiency of methods for isolating mutants without the reliance on a predicted phenotype. Established PCR-based methods of isolating deletion mutants are widely used for this purpose in Caenorhabditis elegans. However, these methods are inefficient at isolating small deletions. We report here a novel modification of PCR-based methods, employing thermostable restriction enzymes to block the synthesis of wild-type PCR product, so that only the deletion PCR product is amplified. This modification greatly increases the efficiency of isolating small targeted deletions in C.elegans. Using this method six new deletion strains were isolated from a small screen of approximately 400 000 haploid genomes, most with deletions <1.0 kb. Greater PCR detection sensitivity by this modification permitted ∼10-fold greater pooling of DNA samples, reducing the effort and reagents required for screens. In addition, effective suppression of non-specific amplification allowed multiplexing with several independent primer pairs. The increased efficiency of this technique makes it more practical for small laboratories to undertake gene knock-out screens.